Polarographic evaluation of mitochondrial enzymes activity in isolated mitochondria and in permeabilized human muscle cells with inherited mitochondrial defects - Wenchich, L; Drahota, Z; Honzík, T; Hansíková, H; Tesarová, M; Zeman, J; Houstek, J (Physiological research, 2003)
Inherited disturbances of the mitochondrial energy generating system represent a heterogeneous group of disorders associated with a broad spectrum of metabolic abnormalities and clinical symptoms. We used the polarographic and spectrophotometric method for detection of mitochondrial disorders, because these two techniques provide a different insight into mitochondrial function. In six patients suspected of mitochondrial disease we found defects of complex I (two patients), complex III (one patient), complex IV (two patients) and a combination of defect of complex III and IV (one patient). Citrate synthase activity, used as the reference enzyme, was not changed. A comparison of the two methods showed several differences in evaluation of mitochondrial enzymes activity due to the fact that both methods used different conditions for enzyme activity measurements. In contrast to oxygen consumption measurements, where the function of the whole-integrated respiratory chain is characterized, spectrophotometric measurements characterize activities of isolated complexes in disintegrated membranes. However, it may be concluded from our experiments that both methods provide useful and complementary data about mitochondrial energetic functions. Whereas spectrophotometric data are suitable for evaluation of maximal enzyme activities of mitochondrial enzyme complexes, polarographic data provide better information about enzyme activities in cells with mitochondrial defects under in situ conditions.
Keywords: Infant; Humans; respirační komplex II; Mitochondrial Diseases; Kearnsův-Sayreův syndrom; kojenec; dítě; Oxygen Consumption; Spectrophotometry; Child; permeabilita buněčné membrány; dospělí; lidé; syndrom MELAS; Electron Transport Chain Complex Proteins; Genetic Diseases, Inborn; genetické nemoci vrozené; polarografie; Kearns-Sayre Syndrome; respirační komplex III; předškolní dítě; Adult; kosterní svaly; Electron Transport Complex II; respirační komplex IV; Electron Transport Complex III; elektronový transportní řetězec; Cell Membrane Permeability; Adolescent; Electron Transport Complex I; Muscle, Skeletal; spotřeba kyslíku; spektrofotometrie; MELAS Syndrome; respirační komplex I; mitochondriální nemoci; Electron Transport Complex IV; Mitochondria, Muscle; Child, Preschool; Polarography; svalové mitochondrie; mladiství